Synergistic Effect of the Combination of Commercial Essential Oils with Standard Antibiotics: In vitro Evaluation: Antimicrobial Effect of Essential Oil on Tested Food Isolates - Mehboob, Aneela; Abbas, Tanveer (Biological Sciences - PJSIR, 2020)
The aim of this investigation was to determine the antibacterial activity of essential oils and to assess the outcomes produced by the combinations of antibiotics and essential oils. To execute this research, gold standard and conventional methods were used. Antibacterial potency of five essential oils namely Citrus limon, Elettaria cardamomum, Lavandula angustifolia, Nigella sativa and Prunus dulcis were tested against Escherichia coli, Serratia fonticola, Serratia liquefaciens, Citrobacter freundii and Staphylococcus aureus recouped from street foods of Karachi. Among five of them, Citrus limon and Lavandula angustifolia were the most potent essential oils showing highest antibacterial activity in their undiluted form with the exception of Staphylococcus aureus but their mix at different concentrations successfully inhibited the growth of Staphylococcus aureus and Serratia fonticola. Synergistic outcomes were achieved against all the tested bacterial strains from the mix of essential oils and antibiotics, however antagonistic results were also obtained. This exploration underpins the application of essential oils alone and in combinations with antimicrobial agents to improve the affectability of ineffective drugs and aides in the advancement of new antimicrobial drugs to treat bacterial infections utilizing therapeutic plants.